Interactive visualization of mathematics in 3D web - Lai, Danbo (2013)
We propose a new educational web-enabled 3D shape modeling framework that does not restrict to a list of predefined primitive geometric objects and allows the user to interactively create objects by incremental modifications of the basic shape with the tool shapes that are defined by analytical functions. The shape definition is eventually a function script which can be rendered on any suitable graphics system. The function script includes accelerating structures that significantly improve the shape rendering performance allowing us to sustain interactivity with large number of interactive operations applied.